2017
DOI: 10.1080/2162402x.2017.1379642
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 promotes the development of a CD73-positive Vγ9Vδ2 T cell regulatory population

Abstract: Vγ9Vδ2 T cells contribute to the immune response against many tumor types through their direct cytotoxic activity and capacity to regulate the biological functions of other immune cells, such as dendritic cells and IFN-γ-producing CD8 T cells. However, their presence in the tumor microenvironment has also been associated with poor prognosis in breast, colon and pancreatic cancers. Additionally, recent studies demonstrated that cytokines can confer some plasticity to Vγ9Vδ2 T cells and promote their differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Vγ9Vδ2 T cells with regulatory functions have initially been described by Casetti et al ( 68 ), who reported the in vitro induction of FOXP3 + regulatory Vγ9Vδ2 T cells after pAg stimulation in the presence of TGF-β1 and IL-15. Other groups have confirmed the emergence of regulatory/suppressor Vγ9Vδ2 T cells as a consequence of pAg activation in the presence of selected cytokines ( 69 , 70 ). Ma et al have reported an increased proportion of regulatory Vγ9Vδ2 T cells in the PB of MM patients which could suppress antimyeloma immune responses with the same efficiency of conventional Tregs ( 71 ).…”
Section: Strategies To Rescue Antitumor Vγ9vδ2 T-cell Function In Thementioning
confidence: 84%
“…Vγ9Vδ2 T cells with regulatory functions have initially been described by Casetti et al ( 68 ), who reported the in vitro induction of FOXP3 + regulatory Vγ9Vδ2 T cells after pAg stimulation in the presence of TGF-β1 and IL-15. Other groups have confirmed the emergence of regulatory/suppressor Vγ9Vδ2 T cells as a consequence of pAg activation in the presence of selected cytokines ( 69 , 70 ). Ma et al have reported an increased proportion of regulatory Vγ9Vδ2 T cells in the PB of MM patients which could suppress antimyeloma immune responses with the same efficiency of conventional Tregs ( 71 ).…”
Section: Strategies To Rescue Antitumor Vγ9vδ2 T-cell Function In Thementioning
confidence: 84%
“…We demonstrated that this subset can synthetize adenosine through CD73 enzymatic activity, and produces the suppressive cytokine IL-10 and the chemokine IL-8 (also known as CXCL8) that is involved in the recruitment of polymorphonuclear leukocytes (PMN)-MDSCs. This CD73+ cell subpopulation can suppress the T cell immune response directly in an adenosine-and IL-10-dependent manner, and indirectly by impairing DC antigen presentation (61). We then extended these observations to Vδ1 T cells.…”
Section: Il-21mentioning
confidence: 71%
“…For example, IL-21 enhances IL-10 production by regulatory B cells and their proliferation. Similarly, our group recently found that IL-21 is implicated in the polarization of human Vγ9Vδ2 T cells and Vδ1 T cells toward a regulatory phenotype (30,61). We isolated a subpopulation of CD73+ regulatory Vγ9Vδ2 T cells following their expansion in the presence of IL-21.…”
Section: Il-21mentioning
confidence: 87%
“…To further investigate the role of CD28 stimulation with respect to the induction of suppressive function of Vδ2 + T cells, we analyzed freshly isolated untouched Vδ2 + T cells (purity > 98%, contaminating cells were in the lymphocyte gate in forward versus side scatter (FSC vs SSC) and CD14 negative, thus unlikely monocytes, Supplementary Figure S8) cultivated in wells immobilized with anti-CD28, or anti-TCRγδ or both mAbs and then co-cultured them with autologous T cells stimulated with anti-CD3 mAb (OKT3). Different to in vivo situation where T cell proliferation is dependent on a second signal T cell proliferation solely by OKT3 was already proven in vitro in previous literatures in different settings [51][52][53][54]. Figure 5b illustrates the representative data from one of three donor cultures.…”
Section: Cd28 Stimulation Is Not Essential For Vδ2 + T Cell Suppressimentioning
confidence: 77%